A LASER DOPPLER FLOWMETRY FOR MEASURING THE PULP BLOOD PERFUSION IN TEETH WITH POSTOPERATIVE SENSITIVITY - a case report - Vesela Stefanova; Neshka Manchorova; Desislava Georgieva; Angel Sapundgiev; Yoanna Nikova; Georgy Simeonov; Emina Kaish; Isabela Antipova; Maria Stoyanova; Nikolay Simeonov; Snejana Tzanova; Stoyan Vladimirov (Peytchinski Publishing, 2016)
Purpose: To study the blood perfusion in teeth with post-operative sensitivity. Material and Methods: A twenty years old female came to the Department of Operative Dentistry and Endodontics with complains of postoperative sensitivity in one upper premolar and one lower molar. The teeth were restored by resin-composite restorations and two-step adhesive. Measuring of the pulp blood perfusion of the sensitive teeth and comparing with healthy ones was accomplished by using laser Doppler device moorVMS-LDF2. Pulp vitality was assessed by conventional cold and electrical pulp tests. Subjective symptoms were measured by VAS. Saliva biochemistry was evaluated by Saliva Check Buffer test. Results: The upper premolar, tooth 25, showed 28,5 PU, the lower molar, tooth 36, showed 21,9 PU. The electrical pulp test of teeth was 17 µA and 44 µA respectively. The cold response of teeth was 2,5s and 5,0s. According to VAS, the intensity of pain in tooth 25 is 4,3mm and in tooth 36 2,1mm. Conclusion: Laser Doppler flowmetry is used for the first time for measuring the blood perfusion in teeth with postoperative sensitivity. For revealing the connection between pulp hemodynamic and postoperative sensitivity future studies are needed in which laser Doppler flowmetry can be highly valuable.